2003
DOI: 10.1161/01.res.0000104084.88317.91
|View full text |Cite
|
Sign up to set email alerts
|

Role of 14-3-3-Mediated p38 Mitogen-Activated Protein Kinase Inhibition in Cardiac Myocyte Survival

Abstract: 14-3-3 family members are dimeric phosphoserinebinding proteins that regulate signal transduction, apoptotic, and checkpoint control pathways. Targeted expression of dominant-negative 14-3-3 (DN-14-3-3) to murine postnatal cardiac tissue potentiates Ask1, c-jun N-terminal kinase (JNK), and p38 mitogen-activated protein kinase (MAPK) activation. DN-14-3-3 mice are unable to compensate for pressure overload, which results in increased mortality, dilated cardiomyopathy, and cardiac myocyte apoptosis. To evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 13 publications
(19 reference statements)
2
34
0
Order By: Relevance
“…Mice expressing a dominant-negative form of 14-3-3η (DN-14-3-3) are unable to compensate for pressure overload resulting in increased myocyte apoptosis and mortality. DN-14-3-3/DNp38β mice, and to a lesser extent DN-14-3-3/DN-p38α mice, show reduced mortality and cardiac myocyte apoptosis in response to pressure overload [35]. Taken together, these data indicate that, although expressed at lower levels than p38α or p38γ, p38β plays a distinct role in the heart.…”
Section: Discussionmentioning
confidence: 72%
“…Mice expressing a dominant-negative form of 14-3-3η (DN-14-3-3) are unable to compensate for pressure overload resulting in increased myocyte apoptosis and mortality. DN-14-3-3/DNp38β mice, and to a lesser extent DN-14-3-3/DN-p38α mice, show reduced mortality and cardiac myocyte apoptosis in response to pressure overload [35]. Taken together, these data indicate that, although expressed at lower levels than p38α or p38γ, p38β plays a distinct role in the heart.…”
Section: Discussionmentioning
confidence: 72%
“…For example, it has been reported that the inhibition of T-cell antigen receptormediated Shc-Grb2 signaling complex or the decrease of Grb2 expression in mice result in a defective TCR-induced p38 MAPK activation [97,100]. The 14-3-3 protein has also been reported to participate in the regulation of p38 MAPK activation [102][103][104] and to form a signaling complex with PI3 K [105,106]. Clearly it will be important to determinate other components of the PI3-K-p38 signaling complex to understand the mechnanism of P-selectinmediated β1 integrin activation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that compound transgenic DNp38␣ and DNp38␤ mice display resistance to myocardial injury after pressure overload (28), demonstrating that the enhanced survival observed in these mice is a consequence of p38 MAPK inhibition that is 14-3-3 mediated. To establish whether inhibition of p38 MAPK can reverse the DN 14-3-3 phenotype after swimming stress, we treated DN 14-3-3 mice with FR-167653 (p38 MAPK inhibitor) in the present study.…”
Section: Translational Physiologymentioning
confidence: 92%